Multiple sclerosis and air pollution exposure: Mechanisms toward brain autoimmunity. (March 2017) - Esmaeil Mousavi, Sayed; Heydarpour, Pouria; Reis, Jacques; Amiri, Masoud; Sahraian, Mohammad Ali
Abstract: The association between neurodegenerative diseases and environmental exposures, in particular air pollution, has been noticed in the last two decades, but the importance of this environmental factor in multiple sclerosis (MS) pathogenesis has not been considered extensively. However, recent evidence suggests that major mechanisms involved in MS pathogenesis, such as inflammatory factors expression, free radicals overproduction, the blood brain barrier (BBB) breakdown, neuroinflammation, vitamin D deficiency and mitochondrial dysfunction could also occur due to exposure to air pollutants. A prospective hypothesis is suggested here in which exposure to air pollutants may initiate destructive mechanisms inducing inflammatory-oxidative cascades, reduction of immunological self-tolerance and neurodegeneration leading to brain autoimmunity.